Endoscopic processing: what are the gaps in clinical practice? - Madureira, Rosilaine Aparecida da Silva (2021)
Objective: This paper aimed to identify gaps in clinical practice that interfere with the effectiveness of endoscopic processing. Method: Integrative review of articles published between 2008 and 2020, identified in databases through controlled descriptors in Health Sciences, adopting the PICO strategy. The identified gaps were classified according to the level of evidence (IA, IB, IC, II). Results: Eighteen articles were found, recording 64 gaps, 26.6% at the level of evidence IA and 40.6% IB, predominating: absence/inadequate drying (55.5%), manual cleaning without brushing the inappropriate channels/brushes (50%), omission of the sealing test (38.8%), inadequate storage (33.3%) and use of the disinfectant solution (27.7%), time of immersion or monitoring of the minimum effective concentration, absence of pre-cleaning (16.6%), incorrect transportation to the processing room (11.1%). Conclusion: It was concluded that guidelines strongly recommended by international and national entities have been breached, representing critical aspects in the processing of endoscopes that imply potential failures in patient safety.